The Deep Past as a Social Asset in the Levant (DEEPSAL) - El Abed, O. (Council for British Research in the Levant, 2018)
The aim of the Deep Past as a Social Asset in the Levant (DEEPSAL) project was to understand how local cultural heritage can contribute to people's lives today. The research studied two villages in south Jordan - Beidha and Basta - which contain highly significant Neolithic archaeological sites, representing a period of huge change in human history 9000 years ago, when people first began farming and living in large settled communities. The historic impact of this period is fundamental to how we live today, and the process of settling down, and domesticating barley and goats, has an obvious potential resonance with the lives of the modern communities in the region. This study tries to understand how this 'deep past' can be an asset to the contemporary lives of the communities who live around the sites today.